Hospital and Institutionalisation Care Costs after Limb and Visceral Ischaemia Benchmarked Against Stroke: Long-Term Results of a Population Based Cohort Study. (August 2018) - Luengo-Fernandez, Ramon; Howard, Dominic P.J.; Nichol, Kathleen G.; Dobell, Emily; Rothwell, Peter M.; ,
Abstract : Objective/background: There are few published data on the acute care or long-term costs after acute/critical limb or visceral ischaemia (ACLVI) events. Using data from patients with acute events in a population based incidence study (Oxford Vascular Study), the present study aimed to determine the long-term costs after an ACLVI event. Methods: All patients with first ever incident ACLVI from 2002 to 2012 were included. Analysis was based on follow up until January 2017, with all patients having full 5 year follow up. Multivariate regressions were used to assess baseline and subsequent predictors of total 5 year hospital care costs. Overall costs after an ACLVI event were benchmarked against those after stroke in the same population, during the same period. Results: Among 351 patients with an ACLVI event, mean 5 year total care costs were €35, 211 (SD 50, 500), of which €6443 (18%) were due to long-term institutionalisation. Costs differed by type of event (acute visceral ischaemia €16, 476; acute limb ischaemia €24, 437; critical limb ischaemia €46, 281; p  < 0.001). Results of the multivariate analyses showed that patients with diabetes and those undergoing above knee amputations incurred additional costs of €11, 804 ( p  = 0.014) and €25, 692 ( p  < 0.001), respectively. Five year hospital care costs after an ACLVI event were significantly higher than after stroke (€28, 768 vs. €22, 623; p  = 0.004), but similar after including long-term costs of institutionalisation (€35, 211 vs. €35, 391; p  = 0.957). Conclusion: Long-term care costs after an ACLVI event are considerable, especially after critical limb ischaemia. Hospital care costs were significantly higher than for stroke over the long term, and were similar after inclusion of costs of institutionalisation.